Strengthening Southern Hemisphere Westerlies and Amundsen Sea Low Deepening Over the 20th Century Revealed by Proxy‐Data Assimilation. Issue 24 (10th December 2021) - O'Connor, Gemma K.; Steig, Eric J.; Hakim, Gregory J.
Abstract: Winds and pressure over the Southern Ocean are critical to many aspects of the climate system, but the brevity of climate data in this region makes it challenging to interpret recent changes. Here, we reconstruct 20th century sea level pressure and zonal surface wind anomalies over the Southern Ocean, using data assimilation with a global paleoclimate proxy database and four climate‐model priors. The reconstructions agree well with instrumental reanalysis products, especially in the circumpolar westerly and Pacific regions. We observe significant strengthening in the midlatitude Pacific westerlies, associated with a deepening Amundsen Sea Low, throughout the 20th century in all four reconstructions. When the prior includes anthropogenic forcing, we observe poleward‐shifting circumpolar westerlies throughout the 20th century. Our results highlight the combined roles of natural variability and anthropogenic forcing, and the zonally asymmetric character of atmospheric circulation changes at high southern latitudes, with implications for Antarctic ice sheet change. Plain Language Summary: Wind and pressure patterns over the Southern Ocean modulate ocean carbon uptake and may influence the stability of the Antarctic ice sheet. Observations suggest that westerly winds around Antarctica are strengthening and shifting closer to Antarctica. However, modern instrumental observations (i.e., data from satellites, radiosondes, and weather stations) in this region begin only in 1979, making it difficult to place these changes in the context of natural climate variability over longer timescales. Here, we use paleoclimate proxy records (e.g., oxygen‐isotope records from ice cores), combined with simulations from climate models, to produce maps of surface pressure and winds over the Southern Ocean spanning the 20th century. Our results compare well with available independent data sets. We find that strengthening westerly winds in the Pacific sector of the Southern Ocean has occurred through most of the 20th century and is associated with a deepening of the Amundsen Sea Low. Our results suggest that this is accompanied by poleward‐shifting westerly winds around the rest of Antarctica, attributable to anthropogenic forcing (i.e., increased greenhouse gases). Key Points: Paleoclimate proxy‐data assimilation skillfully reconstructs sea level pressure and surface winds in the high latitude Southern Hemisphere Reconstructions show 20th century Amundsen Sea Low deepening and strengthening circumpolar westerlies, particularly in the Pacific sector Twentieth century poleward‐shifting circumpolar westerlies are observed only when anthropogenic forcing is included in the climate‐model prior